2014
DOI: 10.1209/0295-5075/106/59001
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of the particle fluxes from the thunderclouds: Energy spectra analysis

Abstract: Simultaneous measurements of the gamma ray differential energy spectra, electric field disturbances, and meteorological conditions provided by experimental facilities located at Mt. Aragats in Armenia allows to establish the model of particle acceleration and propagation in thunderstorm atmosphere. We present comparisons of measured and modeled thunderstorm ground enhancements (TGEs). The origin of the majority of TGEs is the MOS process -the modification of energy spectra of cosmic ray electrons in the atmosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 18 publications
3
32
0
Order By: Relevance
“…For these locations we will consider two mechanisms for producing the glow and in both cases we assume that it is the cosmic background flux that is enhanced. The first one is similar to the MOS mechanism suggested by Chilingarian et al (, ) for explaining the Thunderstorm Ground Enhancements but here applied to higher altitudes. This idea builds on the ideas suggested earlier by McCarthy and Parks () to explain the first glow observations from the early 1980s (McCarthy & Parks, ; Parks et al, ).…”
Section: Modeling Glow Production Mechanismssupporting
confidence: 68%
See 2 more Smart Citations
“…For these locations we will consider two mechanisms for producing the glow and in both cases we assume that it is the cosmic background flux that is enhanced. The first one is similar to the MOS mechanism suggested by Chilingarian et al (, ) for explaining the Thunderstorm Ground Enhancements but here applied to higher altitudes. This idea builds on the ideas suggested earlier by McCarthy and Parks () to explain the first glow observations from the early 1980s (McCarthy & Parks, ; Parks et al, ).…”
Section: Modeling Glow Production Mechanismssupporting
confidence: 68%
“…This mechanism requires field strength of just a fraction of E t but gives the cosmic background electron and positron sufficient extra energy to produce enhanced fluxes of gamma rays. The spectral shape resulting from RREA and MOS was also investigated by Cramer et al () who found similar spectral behavior as reported by Chilingarian et al ().…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Cramer et al [] found that as the electric field approaches the runaway electron threshold value, the solution to the electron energy spectrum is a convolution between a power law function and a Gaussian distribution [see Cramer et al , , equation (39)]. At the same time, it is worth mentioning that even if the power law fits seem not to be correct at relatively high fields above δ = 1.05, as it was shown by Chilingarian et al [, ], most of the measured TGEs correspond to lower field cases, where power law still applies. Moreover, it was shown that most of the TGEs or glows occur under fields below the runaway threshold, so called Modification of Spectra (MOS) process [ Chilingarian et al , ].…”
Section: Effects Of Electron Propagation Length and Field Strengthmentioning
confidence: 99%
“…For most of the TGE glows, only gamma ray spectra are possible to estimate. At the same time, the estimations of Chilingarian et al [] showed that some of the events correspond to cases where the electric fields are lower than the critical field necessary for the RREA initiation. This process is termed Modification of Spectra (MOS), when secondary cosmic ray electron spectra are modified without an avalanche multiplication process earlier suggested by Chilingarian et al [].…”
Section: Introductionmentioning
confidence: 99%